INDAHNYA TOLERANSI DALAM SEMANGKOK SOTO (KAJIAN GASTRONOMI SASAK SOTO CHI CHANG AMPENAN) - Ajuar Abdullah; Wiwik Nirmala Sari; Ulfan Mulyawan (Journal Of Responsible Tourism, 2021)
Soto Chi Chang is one of the legendary Sasak cuisines from the 1950s and still survives to this day. Soto chi chang, which is sold on the overhang of a shop near the entrance to the main area of the Old Town of Ampenan, is in great demand by various groups, from ordinary people to officials in Mataram City. This is inseparable from the strength of taste and the strength of the history of Soto chi chang which can last for 72 years from 1950 to 2022. This potential attraction has prompted researchers to conduct research on the value of tolerance and gastronomic appeal in a bowl of Soto chi chang. The research method used is the descriptive qualitative method by describing the value of tolerance and gastronomic appeal in the form of a scientific narrative. The result of the research is that Soto chi chang uses various types of spices and mixtures of various types of food ingredients. Seasonings and foodstuffs characterize the characteristics of various ethnic groups such as the Chinese ethnicity as Kong Chi Chang's identity, Bugis-Makassar-Sasak culture as the cultural heritage of Kong Chi Chang's environment, forming the uniqueness of Soto chi chang which is different from other Soto in general. The diversity of spices and food ingredients used in a bowl of Soto provides a delicious taste for Soto chi chang connoisseurs. The beauty and enjoyment of the Soto reflect the beauty of the cultural diversity of ethnic groups that coexist peacefully in the Ampenan Old Town area. The highest wealth of Sasak gastronomy contained in Soto chi chang is the historical value as a silent witness to the glory of Ampenan Old Town in the 1950s era.